Biogenic green synthesis of zinc oxide nanoparticles from defatted coconut presscake for wastewater treatment - A’bas, Nurain Afina; Rathi, Devi-Nair Gunasegavan; Meli, Abubakar Dantani; Abdelmonem, Mohamed; Che Abdullah, Che Azurahanim; Abu, Afidah; Shukri, Radhiah (Hibiscus, 2024)
Defatted coconut meat presscake is a by-product of coconut milk production, often discarded or used as low value products, but has the potential to treat wastewater. The aim of this study was to characterize zinc oxide nanoparticles (ZnO NPs) from defatted coconut meat presscake and determine its effect on the degradation of contaminants in wastewater and antibacterial properties. The nanoparticles were created via a co-precipitation method using zinc nitrate as a precursor and defatted coconut meat presscake extract as a reducing agent. The characteristics of the nanoparticles were then characterized using FTIR (Fourier Transform Infrared Spectroscopy), FE-SEM (Field-Emission Scanning Electron Microscopy), XRD (X-ray diffraction), and TGA (Thermogravimetric Analysis). Characterization revealed ZnO NPs with a hexagonal wurtzite structure and an average size of 54 nm. The photocatalytic degradation of methylene blue under UV light irradiation showed a degradation efficiency of 79.5 % within 180 min. Treated wastewater with Zn ONPs at concentrations of 0.5, 1, and 5 mg/L showed a significantly reduced microbial load, with an average of 10.2×106, 8.3×106 and 3.8×106 CFU/mL, respectively compared to untreated wastewater (16.5×106 CFU/mL), indicating the antimicrobial properties of ZnO NPs. Therefore, ZnO NPs, synthesized from defatted coconut meat presscake extract, offer an eco-friendly solution for efficiently treating wastewater from food industry.